THE ? ???? IN JOSHUA 6 AND 7, INFLUENCED BY P? - E E Meyer (Acta Theologica)
The article engages with the old question of Priestly influence in the book of Joshua and is, to a large extent, a response to Dozeman’s most recent commentary on Joshua 1-12. The article focusses specifically on the ? ???? and argues that there are more intertextual links between the understanding of ? ???? in Joshua 6 and 7 and texts from Deuteronomy and the Former Prophets than with Priestly texts.